STUDI PENDAHULUAN PENGAWETAN ROTAN BAHAN BAKU MEBEL - Barly Barly (Jurnal Penelitian Hasil Hutan, 1991)
Rattan for the furniture  raw materials is easily attacked by stain fungi and moulds during air  drying, leaving discolored  surfaces.  The soft portion is also susceptible to attack of powder post beetles. To prevent this problem, the newly cut rattan should be  treated with preservative to ensure  a reasonable service life. The treatment   method affects the extent of penetration and absorption of  preservation  into the rattan. The rasult of study  on the preservation  of rattan by pressure process is presented  in this paper. A  pressure   period for 5, 15, and 25  minutas  was sufficient  to obtain required retention of preservative for the rattan tabu-tabu, batang and tohiti.